Comparison of Per Cent Predicted and Percentile Values for Pulmonary Function Test Interpretation - Smita Pakhale; Zoheir Bshouty; Theodore K Marras (Canadian Respiratory Journal)
BACKGROUND: Pulmonary function tests (PFTs) are commonly interpreted as a fraction of predicted normal values, with an abnormal test often defined as less than 80% or greater than 120% of the predicted value. However, recommendations of the American Thoracic Society/European Respiratory Society suggest using a percentile-based approach to define an abnormal test (less than the fifth or greater than the 95th percentiles).